Electronic cigarettes for adults with tobacco dependence enrolled in a tobacco treatment program: A pilot study. (May 2018) - Baldassarri, Stephen R.; Bernstein, Steven L.; Chupp, Geoffrey L.; Slade, Martin D.; Fucito, Lisa M.; Toll, Benjamin A.
Abstract: Introduction: Electronic cigarettes (ECs) have emerged as a potential harm-reducing alternative for tobacco smokers. However, the role ECs might play in treatment settings is unclear. We conducted an exploratory study of treatment-seeking smokers enrolling in a standard tobacco treatment program who were provided with either a nicotine or non-nicotine EC to use as needed to cease tobacco smoking. Methods: Treatment-seeking smokers received standard tobacco treatment for 8 weeks and were given nicotine transdermal patch therapy, behavioral counseling, and either a nicotine or non-nicotine EC to use as needed. Smoking and EC use patterns were tracked longitudinally to week 24. Results: 40 subjects were enrolled into the study. At week 24, 6 subjects (15%) were abstinent, and the mean reduction in reported cigarettes smoked per day was 6.8 ± 12. There were no significant differences in smoking outcomes between those who received a nicotine or non-nicotine EC (proportion abstinent at 24 weeks: nicotine EC = 4/20 (20%); non-nicotine EC = 2/20 (10%); p = 0.66). Among subjects assessed at follow-up, 62.5% were EC non-users. Conclusions: The addition of a 2nd generation EC to outpatient tobacco treatment among tobacco smokers is feasible. Among those who quit smoking, half were still using the EC at 6-month follow-up. Appeal of the EC among smokers was variable, and those who had quit smoking tended to switch to lower strength nicotine solutions. Further research is needed to determine whether ECs can reduce harm and be an effective adjunct to existing tobacco treatment interventions. Highlights: Electronic cigarettes can be incorporated into a tobacco treatment program. Half of the smokers who quit cigarettes were using e-cigarettes at follow up. Low or zero strength nicotine e-liquids were preferred by some smokers. Behavioral cues of e-cigarettes were important for modifying smoking behavior.